Cryptococcosis caused by cryptococcus gattii: 2 case reports and literature review. Issue 50 (11th December 2020) - Xue, Xinying; Deng, Hui; Zhao, Longting; Zang, Xuelei; Asuquo, Idorenyin Polycarp; Meng, Mingming; Ma, Xidong; Qin, Chong; Meng, Yao; Wu, Chongchong; Gao, Jie; Pan, Lei
Abstract : Abstract: Cryptococcosis caused by Cryptococcus gattii, is a life threatening fungal infection with recently increasing prevalence. C. gattii is a species complex comprising multiple independent species. However, many biological characteristics and clinical features of cryptococcosis due to C. gattii are relatively less well defined. In this paper, we identify two cases of C. gattii infection, and laboratory findings of genotype VGI and VGII in two groups of apparently immunocompetent Chinese individuals respectively. Upon detailed review of all 35 cases of C. gattii infections, it was observed that C. gattii can cause debilitating illness in both immunocompetent and immunocompromised individuals. Cryptococcosis due to C. gattii is a serious systemic fungal infection, with pulmonary central nervous system tropism. Epidemiologically, C. gattii infection is not only restricted in tropical and subtropical regions, but also in other geographical settings.